Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 6 - Section 6.3 - Equations with Parentheses - Exercises: 50

Answer

x=1

Work Step by Step

Simplifying -2x + 6(2 + -1x) + -4 = 3(x + 1) + -6 -2x + (2 * 6 + -1x * 6) + -4 = 3(x + 1) + -6 -2x + (12 + -6x) + -4 = 3(x + 1) + -6 Reorder the terms: 12 + -4 + -2x + -6x = 3(x + 1) + -6 Combine like terms: 12 + -4 = 8 8 + -2x + -6x = 3(x + 1) + -6 Combine like terms: -2x + -6x = -8x 8 + -8x = 3(x + 1) + -6 Reorder the terms: 8 + -8x = 3(1 + x) + -6 8 + -8x = (1 * 3 + x * 3) + -6 8 + -8x = (3 + 3x) + -6 Reorder the terms: 8 + -8x = 3 + -6 + 3x Combine like terms: 3 + -6 = -3 8 + -8x = -3 + 3x Solving 8 + -8x = -3 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 8 + -8x + -3x = -3 + 3x + -3x Combine like terms: -8x + -3x = -11x 8 + -11x = -3 + 3x + -3x Combine like terms: 3x + -3x = 0 8 + -11x = -3 + 0 8 + -11x = -3 Add '-8' to each side of the equation. 8 + -8 + -11x = -3 + -8 Combine like terms: 8 + -8 = 0 0 + -11x = -3 + -8 -11x = -3 + -8 Combine like terms: -3 + -8 = -11 -11x = -11 Divide each side by '-11'. x = 1 Simplifying x = 1
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.